Promoting Dolichoderus thoracicus as an Agent to Disperse Trichoderma sp., a Fungus that Controls the Black Pod Disease, Central Sulawesi, Indonesia - Tjandra Anggraeni; U. Umrah; Rizkita R. Esyanti; I Nyoman P. Aryantha (Institute for Research and Community Services (LPPM) ITB, 2014)
In this study, we propose to use Dolichoderus thoracicus to act as a double agent; not only as an agent to control cocoa plant pests, but also as an agent for distributing Trichoderma sp., a fungus that suppresses the development of the black pod disease caused by Phytophthora palmivora. In the experiments, D. thoracicus was more attracted to honey-soil media (M5) and coconut waste pulp-soil media (M6). However, 10% sucrose-potato-soil media (M3) was the best media for growing Trichoderma sp. Morphological study showed that spores attached to many parts of D. thoracicus. The efficiency of D. thoracicus in distributing the spores compared to the conventional method of using a sprayer was measured. The results showed that the growth of P. palmivora was suppressed by 83.33%, which is not significantly different from when Trichoderma was dispersed through spraying (87% suppressed). It was concluded that D. thoracicus can act as a double agent and can be used to disperse Trichoderma sp.